Origin of the criteria for the visibility of the lunar crescent in Malaysia - Mohd Saiful Anwar, M.N.; Saadan, M.; Mohd Zambri, M.Z. (2015)

(untitled)
The expected visibility (imkan al-rukyah) criteria have been applied to determine the first month of the Islamic calendar in Malaysia since 1984. This paper aims to investigate chronologically the process behind the decision to formulate the criteria, and provide an analysis of the official documents and interviews. This will be followed by a general overview of the development of such criteria in Malaysia. Based on its astronomical background, the authors suggest that the criteria were adopted from the Istanbul Resolution 1978 and formulated according to the reports produced by the Indonesian religious authorities concerning the sighting of the moon.